GCNF-dependent activation of cyclin D1 expression via repression of Mir302a during ES cell differentiation - Wang, Hongran (2014)
Cyclin D1 plays an important role in the regulation of cellular proliferation and its expression is activated during gastrulation in the mouse, however, it remains unknown how cyclin D1 expression is regulated during early embryonic development. Here we define the role of germ cell nuclear factor (GCNF) in the activation of cyclin D1 expression during embryonic stem (ES) cell differentiation as a model of early development. During our study of GCNF knock out (GCNF(−/−)) ES cells, we discovered that loss of GCNF leads to the repression of cyclin D1 activation during ES cell differentiation. This was determined to be an indirect effect of de-regulation Mir302a, which is a cyclin D1 suppressor via binding to the 3`UTR of cyclin D1 mRNA. Moreover, we showed that Mir302 is a target gene of GCNF that inhibits Mir302 expression by binding to a DR0 element within its promoter. Inhibition of Mir302a using Mir302 inhibitor during differentiation of GCNF(−/−) ES cells restored cyclin D1 expression. Similarly over-expression of GCNF during differentiation of GCNF(−/−) ES cells rescued the inhibition of Mir302a expression and the activation of cyclin D1. These results reveal that GCNF plays a key role in regulating activation of cyclin D1 expression via inhibition of Mir302a.